POM analyses, immunomodulatory, cytotoxic activities and polyphenolic constituents of Callistemon viridiflorus fruits - Mohamed I.S. Abdelhady; Amel M. Kamal; Mohamed F. Barghash (Faculty of Pharmacy, Cairo University, 2018)
Phytochemical study on 80% ethanolic extract of Callistemon viridiflorus Sims fruits (CVF) resulted in isolation of five phenolic compounds 1; Gallic acid, 2; Ellagic acid, 3; Reynoutrin, 4; Methoxy ellagic acid, 5; Quercetin. Petra/Osiris/Molinspiration (POM) analyses predicted that Reynoutrin and Quercetin have interesting potential activities, also Reynoutrin is found to be safer in relation to Quercetin. 80% ethanolic extract of CVF, Reynoutrin and Quercetin displayed remarkable immunomodulatory activity, as increased proliferation of RAW 264.7 macrophage cells by 1.48, 1.51 and 1.46 fold respectively. 80% ethanolic extract of the C. viridiflorus fruits showed significant cytotoxic activity against P388 leukemia cells (IC50 = 15.11 µg/ml), followed by Quercetin (IC50 = 21.5 µg/ml) then Reynoutrin (IC50 = 33.32 µg/ml). Keywords: POM analyses, Callistemon viridiflorus, Polyphenols, Immunomodulatory, Cytotoxic